Diabetes-Related Complications and Mortality in Patients with Atrial Fibrillation Receiving Different Oral Anticoagulants - Laeeq Ur Rehman, Komal Mushtaq, Haseeb Amjad (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Globally, cardiovascular disease is the main contributor to mortality, accounting for about 17.5 million deaths, or 46.2% of deaths from non-communicable diseases. Objectives: The main objective of the study is to find the diabetes-related complications and mortality in patients with atrial fibrillation receiving different oral anticoagulants. Material and methods: This cross sectional study was conducted in DHQ Teaching Hospital Sahiwal during July 2021 till December 2021. The data were collected from 120 diabetic patients who diagnosed with AF. After permission from hospital ethical committee, total 120 patients meeting the inclusion and exclusion criteria was enrolled in the study. Detailed history of DM and physical examination was done to meet the inclusion and exclusion criteria. Results: The data was collected from 120 patients. Out of 120 participants, 60 were treated with warfarin while 60 were considered as control group. Median age was 26 years in the group I and 25.3 years in the group II (p=0.705). Female cases counted for 41 (86%) and 19 (14%) in I and II groups, respectively. Conclusion: It is concluded that patients with AF and diabetes have a high overall cardiovascular risk. Non–vitamin K antagonist oral anticoagulants were associated with lower hazards of diabetes complications and mortality than warfarin in patients with AF and DM.